Statistical optimization of biohydrogen production from palm oil mill effluent by natural microflora - Rasdi, Zatilfarihiah; Abdul Rahman, Nor'aini; Abd. Aziz, Suraini; Phang, Lai Yee; Mohd Yusoff, Mohd Zulkhairi; Chong, Mei Ling; Hassan, Mohd Ali (Bentham Open, 2009)
In this study, palm oil mill effluent (POME) was used as the substrate for biohydrogen production. Heat-treated POME sludge acclimated with POME incubated at 37°C for 24 hours was used as seed culture. Preliminary screening on the effects of inocula sizes, heat treatment, substrate concentration and pH of incubation by using a factorial design (FD) were conducted under mesophilic condition (37°C) using a serum vial (160 mL). The experimental results from two-level FD showed that pH and Chemical Oxygen Demand (COD) of POME significantly affected biohydrogen production. Op-timizations of the specific hydrogen production (Ps) and the hydrogen production rate (Rm) were achieved by using a central composite design(CCD). The maximum Ps of 272 mL H2/g carbohydrate was obtained under optimum conditions of pH 5.75 and substrate concentration of 80 g/L. The maximum Rm of 98 mL H2/h was calculated under the optimum conditions of pH 5.98 and substrate concentration of 80 g/L. The optimized conditions obtained were subjected to a confirmation run and it showed reproducible data with a Ps of 226 mL H2/g carbohydrate and Rm of 72 mL H2/h.